Perceived Health Benefits of Sports Participation on Intellectual and Social Well-being of the Undergraduate Students in Ado-Ekiti, Nigeria - Jaiyesimi, Boluwaji Gbenga (Àgídìgbo: ABUAD Journal of the Humanities, 2014)
This study is a survey to find out the perceived health benefits of sports participation on the intellectual and social well-being of university undergraduates. The descriptive survey research design was employed for the study while self-structured modified questionnaire was used to elicit information from the respondents. The simple random sampling technique was used to select the sample from the target population which comprised the students of Afe Babalola University, Ado-Ekiti, Nigeria. The total of two hundred and thirty-one (231) respondents participated in the study forming the sample size for the study. The statistical tools used for the study included the percentage counts, frequency, and standard deviation. It was concluded that sports participation in the university should be encouraged by the stakeholders for the promotion of intellectual and social well- being of the students. And that sports participation should not only be regarded as extracurricula activities but as an integral part of the school curriculum for total development